2016
DOI: 10.1155/2016/4575437
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal High-Speed Videoendoscopy: Sensitivity of Objective Parameters towards Recording Frame Rate

Abstract: The current use of laryngeal high-speed videoendoscopy in clinic settings involves subjective visual assessment of vocal fold vibratory characteristics. However, objective quantification of vocal fold vibrations for evidence-based diagnosis and therapy is desired, and objective parameters assessing laryngeal dynamics have therefore been suggested. This study investigated the sensitivity of the objective parameters and their dependence on recording frame rate. A total of 300 endoscopic high-speed videos with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
1
26
1
3
Order By: Relevance
“…Common laryngoscopic examinations are performed by the use of 2D imaging techniques such as stroboscopy, videokymography, and high‐speed videoendoscopy (HSV) . As shown in Figure , the recordings are intrinsically limited to resolve the lateral and longitudinal view of the vocal folds' behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common laryngoscopic examinations are performed by the use of 2D imaging techniques such as stroboscopy, videokymography, and high‐speed videoendoscopy (HSV) . As shown in Figure , the recordings are intrinsically limited to resolve the lateral and longitudinal view of the vocal folds' behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Common laryngoscopic examinations are performed by the use of 2D imaging techniques such as stroboscopy, videokymography, and high-speed videoendoscopy (HSV). [19][20][21][22][23][24] As shown in Figure 1, the recordings are intrinsically limited to resolve the lateral and longitudinal view of the vocal folds' behavior. By these means, the majority of vocal fold pathologies, such as neoplasia, paresis, inflammation, malformation, and atrophy, are recognizable.…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2018, 8, 2666 3 of 17 both can be influenced by different factors [34][35][36][37][38]. One of these factors is the recording frame rate, which was already investigated for acoustic and GAW signals.…”
Section: Introductionmentioning
confidence: 99%
“…For acoustic measures, a sampling frequency of at least 26 kHz was suggested to avoid the introduction of errors [34]. For GAW signals it is reported that up to 90% of parameters were affected by the changes in the frame rate [35]. That study suggested that normative parameter values based on the recording frame rate should be determined and a recording frequency of 4000 Hz seemed to be too low to register all details of vocal fold vibratory patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Typical vocal fold vibrations display a frequency in the range of 80-300 Hz for normal phonation. In order to capture such rapid movements adequately, high-speed videoendoscopy (HSV) with frame rates in the range of 4-20 kHz is used [3][4][5][6][7]. In the clinical routine, the most common methods for an evaluation of the vocal fold physiology and dynamical behavior are based on endoscopic, two-dimensional imaging (see Figure 1, left).…”
Section: Introductionmentioning
confidence: 99%